Discovery of immune responsive proteins in IHHNV-infected and non-infected Macrobrachium rosenbergii / Tahereh Alinejad - Alinejad, Tahereh (2011)
The major problem in the prawn industry worldwide is acute epizootic diseases that are closely associated with explosive death among prawns which leads to economic losses in commercial aquaculture and posing threats to the indigenous wild stocks. Infectious Hypodermal and Hematopoietic Necrosis Virus (IHHNV) was listed by OIE (Office of International Epizootics of World Organization for Animal Health) to be shown to have international significance in aquaculture. The study was conducted to understand the molecular responses of crustacean hemocytes to IHHNV infection. 2D-proteomic approach was used to investigate the differential expression proteins in hemocytes of infected and non-infected M.rosenbergi .Viral DNA screening has been done to identify infected (I) and non-infected (NI) samples by using IHHNV specific primer 309. The protein concentration of the serum to run on IPG-strip was determined using Bradford assay. To avoid protein degradation cup-loading method was used to perform IEF and consequently followed by 12.5% SDS-PAGE gel electrophoresis stained in silver nitrate. The protein identification has been done using MALDI TOF-TOF Mass spectrometry Statistical analysis was performed to infer the differential expressed proteins between the infected and non-infected prawns. Analysis revealed that 20 differentially expressed protein (10 up-regulated, 10 down-regulated) were identified. Finally, after database searches, these 20 proteins were categorized into 8 groups according to their function within the cell. These were proteins associated with energy production and catabolism (14%), cell function and physiology (14%), cell structure (5 %), ATP-buffering and environmental stress (5%), antioxidants (5%), calcium homeostasis (5%), oxygen transportation (19%) and immune system related protein (33%).